1985
DOI: 10.1042/bj2290167
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of rabbit muscle phosphoglycerate mutase by limited proteolysis with thermolysin

Abstract: Rabbit muscle phosphoglycerate mutase is inactivated by proteolysis with thermolysin. Inactivation is correlated with the breakage of one (or a few) bond(s) near one end of the polypeptide chain. There is no change in the overall conformation, quaternary structure or binding to Cibacron Blue on proteolysis. The possible analogy with the existence of a flexible tail in the yeast enzyme is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The C-terminal tail is particularly susceptible to proteolysis, and a phosphoglycerate mutase molecule which has lost these residues, but is otherwise apparently unmodified shows complete loss of mutase activity. These observations have been noted for both the yeast enzyme (Sasaki et al, 1966;Winn et al, 1981) and the rabbit muscle enzyme (Price et al, 1985b). The proteolyzed yeast mutase retains phosphatase activity toward 2,3-bisphosphoglycerate and can thus still bind the bisphospho ligand.…”
Section: C-terminal Tailmentioning
confidence: 61%
“…The C-terminal tail is particularly susceptible to proteolysis, and a phosphoglycerate mutase molecule which has lost these residues, but is otherwise apparently unmodified shows complete loss of mutase activity. These observations have been noted for both the yeast enzyme (Sasaki et al, 1966;Winn et al, 1981) and the rabbit muscle enzyme (Price et al, 1985b). The proteolyzed yeast mutase retains phosphatase activity toward 2,3-bisphosphoglycerate and can thus still bind the bisphospho ligand.…”
Section: C-terminal Tailmentioning
confidence: 61%
“…4(a). There is no significant further change in the spectrum when the concentration of GdnHCl is raised to 4 M. The spectra can be compared with those previously published for the baker's yeast and rabbit muscle enzymes (Hermann et al, 1983;Price et al, 1985b By the analysis of Siegel et al (1980), which depends on the values of 0 over a range of wavelengths from 210 to 240 nm, the percentage of helical structure can be estimated as 27.9 + 1.6, 39.8 + 1.6 (S. pombe dialysed and undialysed respectively), 12.2+1.9 (baker's yeast) and 9.7 + 2 (rabbit muscle). It should be noted that the percentage helical structure for the baker's-yeast enzyme derived from c.d.…”
Section: Stability Of S Pombe Phosphoglycerate Mutasementioning
confidence: 99%
“…In previous work with the rabbit muscle enzyme (Price et al, 1985b) it was also found that the phosphorylated form of the enzyme was less susceptible to proteolysis by thermolysin than the dephosphoenzyme. is a small (< 15%) but reproducible increase in activity at concentrations of GdnHCl up to 0.5 M, followed by a sharp decline in the range 0.5-1.5 M, with 50% activity lost at 0.85 M-GdnHCl.…”
Section: Stability Of S Pombe Phosphoglycerate Mutasementioning
confidence: 99%
“…The lack of or relatively low PGM activity of YhfR is somewhat surprising, given the sequence homology of this protein with dPGMs including the enzyme from S. cerevisiae noted above. However, the yeast enzyme has 36 internal residues not present in YhfR, and the sequences in the carboxy-terminal regions of the two proteins are very different; there are also a variety of data indicating that the carboxy-terminal regions of dPGMs are important for enzyme function (18,24,25,27). In addition, comparison of putative dPGM sequences from Bacillus stearothermophilus, B. subtilis, Clostridium acetobutylicum, and Clostridium difficile, all of which are spore formers, showed a surprising lack of sequence conservation, with only ϳ13% identical residues in the proteins from these four species (data not shown).…”
mentioning
confidence: 99%